STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA PADA PESERTA DIDIK KELAS IX A SMP NEGERI 7 SAMBAS TAHUN PELAJARAN 2024-2025 - Rangga Lawe; Sumar’in; Hadisa Putri (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This research discusses the strategies of Islamic Religious Education teachers in instilling the values of religious moderation in class IX A students of SMP Negeri 7 Sambas for the 2024-2025 academic year. This study aims to determine the strategies used by Islamic Religious Education teachers in instilling religious moderation values and to identify supporting and inhibiting factors in the implementation process. This study uses a qualitative approach with descriptive methods. Data collection techniques used include observation, interviews, and documentation. The results showed that the strategies implemented by Islamic Religious Education teachers in instilling religious moderation values were carried out through exemplary behavior, habituation, advice, reflective learning strategies, and integration of moderation values in the learning process. Supporting factors include school environmental support, cooperation among teachers, and students’ awareness of tolerance values. Meanwhile, inhibiting factors include differences in students’ backgrounds and external environmental influences. Through these strategies, students gradually developed attitudes of tolerance, mutual respect, and appreciation for differences in the school environment.